Effect of physical form of diet on ruminal microbial and metabolic development in young calves - Beharka, A.A.; Nagaraja, Tiruvoor G.; Morrill, J.L. (Kansas Agricultural Experiment Station, 2011)
Eight, ruminally cannulated, newborn, Holstein, bull calves were assigned to receive either finely ground or unground (chopped hay and normally ground grain) diet to study the effects of diet form on ruminal microbial and metabolic development. The difference in diet particle size caused a difference in ruminal pH and a shift in the bacterial population, as evidenced by decreased cellulolytic and increased amylolytic bacterial counts for the ground diet.
The 1990 Annual KSU Dairy Day is known as Dairy Day, 1990
Keywords: Diet; Ruminal microbial; Metabolic development; Calves